Evolution of mitochondrial TAT translocases illustrates the loss of bacterial protein transport machines in mitochondria - Petrů, Markéta; Wideman, Jeremy; Moore, Kristoffer; Alcock, Felicity; Palmer, Tracy; Doležal, Pavel (BMC biology, 2018)
BACKGROUND: Bacteria and mitochondria contain translocases that function to transport proteins across or insert proteins into their inner and outer membranes. Extant mitochondria retain some bacterial-derived translocases but have lost others. While BamA and YidC were integrated into general mitochondrial protein transport pathways (as Sam50 and Oxa1), the inner membrane TAT translocase, which uniquely transports folded proteins across the membrane, was retained sporadically across the eukaryote tree. RESULTS: We have identified mitochondrial TAT machinery in diverse eukaryotic lineages and define three different types of eukaryote-encoded TatABC-derived machineries (TatAC, TatBC and TatC-only). Here, we investigate TatAC and TatC-only machineries, which have not been studied previously. We show that mitochondria-encoded TatAC of the jakobid Andalucia godoyi represent the minimal functional pathway capable of substituting for the Escherichia coli TatABC complex and can transport at least one substrate. However, selected TatC-only machineries, from multiple eukaryotic lineages, were not capable of supporting the translocation of this substrate across the bacterial membrane. Despite the multiple losses of the TatC gene from the mitochondrial genome, the gene was never transferred to the cell nucleus. Although the major constraint preventing nuclear transfer of mitochondrial TatC is likely its high hydrophobicity, we show that in chloroplasts, such transfer of TatC was made possible due to modifications of the first transmembrane domain. CONCLUSIONS: At its origin, mitochondria inherited three inner membrane translocases Sec, TAT and Oxa1 (YidC) from its bacterial ancestor. Our work shows for the first time that mitochondrial TAT has likely retained its unique function of transporting folded proteins at least in those few eukaryotes with TatA and TatC subunits encoded in the mitochondrial genome. However, mitochondria, in contrast to chloroplasts, abandoned the machinery multiple times in evolution. The overall lower hydrophobicity of the Oxa1 protein was likely the main reason why this translocase was nearly universally retained in mitochondrial biogenesis pathways.
Keywords: Evolution, Molecular; transport proteinů; Escherichia coli; Mitochondrial evolution; Hydrophobicity; mitochondrie; membránové transportní proteiny; Protein transport; TAT translocase; Membrane Transport Proteins; Mitochondria; proteiny z Escherichia coli; Escherichia coli Proteins; Eukaryota; molekulární evoluce; Protein Transport